Internal organizational factors driving digital transformation for business model innovation in SMEs - Chanté van Tonder; Sandra Hasanefendic; Bart Bossink; Chris Schachtebeck; Cecile Nieuwenhuizen (Journal of Business Models (JOBM), 2023)
Purpose - The primary purpose of this paper is to investigate which internal organizational factors drive digital transformation for business model innovation in small and medium-sized enterprises (SMEs). Design/methodology/approach - The paper builds on a Delphi study from both a South African and Dutch scholarly and industry perspective. The Delphi study uses a questionnaire to query the commonly cited internal organizational factors that drive digital transformation for business model innovation in SMEs in an emerging and a developed economy. Findings - The paper identifies two important internal organizational factors driving digital transformation for business model innovation in SMEs: (a) a renewal of business strategy and (b) a renewal of business culture. It identifies various subfactors within these two internal organizational factors. Originality/value - The study contributes to the current understanding of the internal organizational factors that drive digital transformation for business model innovation in SMEs. Researchers can use these factors and associated subfactors as a basis for future research. To practitioners, the findings provide a guideline on which business activities in SMEs to (re)arrange to enable digital transformation-induced business model innovation.
Keywords: 650; Business model innovation; Digital transformation; Internal organization; SMEs